Q1-Q4 Journals: Meaning, access, and relevance of global metrics in Nepali context - N Shah, Jay; Malla, Ashesh (Journal of Chitwan Medical College, 2025)
The stratification of academic journals into quartiles (Q1–Q4) based on citation metrics is a global benchmark that directly influences national higher education policy. This editorial examines how this framework intersects with the regulatory mechanisms of Nepal, where bodies like the University Grants Commission (UGC) and the Nepal Medical Council (NMC) explicitly tie academic promotion, research funding, and institutional recognition to publication in indexed, high-quartile journals. We detail these policies, such as the UGC,s Career Advancement Scheme, and critically evaluate the challenges they pose, including systemic bias against local journals and financial barriers for researchers. We argue for a strategic, balanced policy approach that leverages global metrics for quality assurance without stifling regionally relevant research, offering key considerations for policymakers and institutional leaders in Nepal and similar contexts.